New funeral practices in Japan: from the computer-tomb to the online tomb - Duteil-Ogata, Fabienne (Online - Heidelberg journal of religions on the internet, 2015)
Since the 1990’s, Japan has seen its funeral practices become increasingly diverse. New forms appear which will simplify or replace traditional Buddhist practices. Less expensive, these new funeral practices stress the separation between the space of ashes and the space of worship practices, which means a dematerialization of the deceased person. The case study of computer-tomb becoming an online-tomb is a good example of this trend. After a quick overview on Japanese traditional funeral practices to illustrate the context of the computer and online-tombs, I examine in details the features of computer-tomb and online-tombs of several persons and answer to those questions. Are those practices considered as Buddhist practices? How can reality and virtuality be connected together? How is the absence of body managed by the computer-tomb and online-tomb? Does the grave-online appear as the ultimate answer to the funeral proceedings - on a physical and spiritual level - in the Japanese funeral approach?